The effect of the team games tournament model with the traditional game media to train critical thinking ability in elementary school students - Suriya Ningsyih; Hairunisa Hairunisa; Nunung Fatimah; Mariani Ulfa (Department of Mathematics and Science Education, Faculty of Teacher Training and Education, University of Mataram, 2022)
This study aims to determine the effect of the team games tournament (TGT) learning model with the coglak media of areca nut as a traditional game to train the critical thinking skills of the fifth-grade school students in science learning. This research is quantitative research. The one group pretest-posttest design was applied in this study. The sample in this study were the fifth-grade students at SDN Imppres Mawu in academic year 2020/2021. The instrument used is a test using essay questions adapted to critical thinking indicatorsÃ¢â¬âdata analysis using technical analysis of N-Gain test data. N-Gain test is used to calculate students' critical thinking skills. Training students' critical thinking skills obtained an average N-Gain value of 0.32 with a medium category level. In conclusion, there is an influence on the team's games tournament model with the coglak media of areca nut as a traditional game to train students' critical thinking skills to be applied to help train students' critical thinking skills.